Incidence and burden of 671 injuries in professional women footballers: time to focus on context-specific injury risk reduction strategies - Materne, O.; Bennett, F.; Sweeney, A.; Ramsden, J.; Milne, C.; Waller, M.; Chamari, K.; Drust, B. (Research in Sports Medicine, 2025)
This study investigated the extent of injury incidence and burden in a professional women football team of the Scottish Women`s Premier League during two seasons. All injuries causing time-loss or required medical attention were recorded prospectively. A total of 671 injuries, 570 requiring medical attention and 101 causing time-loss were recorded in 41 players. Injuries occurring with National Team resulted in 12% of the club`s international players` lay-off. Overall injury incidence was 11.1/1000-hours and burden was 368.9 days/1000-hours. Injury incidence (23.9/1000-hours vs 8.2/1000-hours) and burden (1049.8 days/1000-hours vs 215.1 days/1000-hours) were higher for match compared to training. Foremost mechanism of match injury burden was indirect-contact, which was different than the non-contact predominantly observed for training injury burden. Injury incidence, burden and patterns differed between training, match and playing positions. Tailoring injury-risk reduction strategies considering context, circumstances and playing position deserve consideration to enhance player`s injury resilience in professional women footballers.